Early experience with a novel transapical transcatheter aortic valve system in patients with severe aortic stenosis: a prospective, multicenter study - Liu, Lulu; Yang, Jian; Zhang, Haibo; Liu, Jian; Zhong, Yucheng; Wei, Lai; Liu, Xianbao; Jian, Zhao; Zhao, Yuan; Guo, Yingqiang (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesRegistered, prospective, multicenter study of the short-term clinical outcomes of a novel transcatheter aortic valve system (Xcor system, Saint Medical Technology, Inc., Nanjing) to evaluate its safety and efficacy.Methods130 high risk patients with symptomatic severe AS from 11 institutions were treated with the novel Xcor system. All patients were pre-TAVR assessed by transthoracic echocardiography and computed tomography of the aortic valve (AV) and relevant left cardiac and vascular anatomy. Procedural, in-hospital, and follow-up clinical outcomes were evaluated after procedures.ResultsThe average age of the 130 patients was 71.2 ± 4.4 years old, 55.4% were male, and the STS score was 8.0 ± 3.9%. Device and procedural success were achieved in 98.5% and 97.7% of the patients, respectively. At 30-day follow-up, all-cause mortality, the incidence of major adverse cardiovascular events, major vascular complications, and new permanent pacemaker implantation were 3.8%, 4.6%, 0.8%, and 0.8%, respectively. 7.7% of patients showed ≥ mild paravalvular leakage, and all 125 (100%) patients were in New York Heart Association Class ≤ II. The procedural and clinical outcomes of bicuspid AV patients were similar to those of tricuspid AV patients.ConclusionsOverall, the 30-day follow-up shows that the procedural outcomes with the novel Xcor system with self-centering support arms are comparable or superior to other contemporary TAVI devices, with a low all-cause mortality, low major adverse cardiovascular events, low PVL and similar clinical outcomes for BAV and TAV patients.